Prevalence of Antinuclear antibody positivity in Thai patients with Rheumatoid arthritis (Eng) - Karoon, Thanaphop; Sornwiboonsak, Pakpiengpen (Thai Journal of Rheumatology, 2025)
Background: Antinuclear antibodies (ANA) are commonly detected in patients with rheumatoid arthritis (RA), although they are traditionally associated with other connective tissue diseases. The prevalence and clinical significance of ANA positivity in RA, particularly among Thai patients remain uncertain. Objective: To investigate the prevalence of ANA positivity and its clinical associations in Thai patients diagnosed with RA. Methods: A retrospective observational study was conducted at Thammasat University Hospital, including RA patients aged ≥18 years from 2014 to 2023. Data on demographics, laboratory parameters including ANA patterns, treatments, disease activity, complications and relapsed disease were collected. Patients were categorized based on ANA status, and comparisons were made between ANA-positive and ANA-negative groups. Results: Among 118 RA patients, ANA positivity was identified in 88.1%. The most frequent ANA pattern was homogenous (50%), followed by fine speckled (34.62%). ANA-positive patients exhibited significantly higher C-reactive protein (CRP) levels (p = 0.002) and were higher prednisolone dosage (p < 0.001). Azathioprine and cyclosporineA usage was exclusive to ANA-positive individuals. No significant differences were observed in demographic characteristics, disease duration, disease activity, remission, relapsed, extra-articular manifestations, or adverse events. Data loss, particularly for ESR and CRP, was noted as a study limitation. Conclusion: ANA positivity is highly prevalent among Thai RA patients and is associated with elevated inflammatory markers and increased immunosuppressive therapy. Further prospective studies are necessary to elucidate the prognostic role of ANA in RA and its potential impact on personalized treatment approaches.